Futsal Coaching - Almeida, João Nuno Alves de (2020)
This study had the goal to analyze expert futsal coaches’ method of decision-making in competitive moments and achieve one better process understanding regarding the preparation game moments, presenting observed thinking patterns. To do this, ten expert and professional coaches’ (M= 46,6 years old and M= 14,3 years of coaching experience) from different countries were interviewed. The questionnaire was semi structured and with two different parts: (a) preparation for decision-making moment during the game; (b) game momentary decision-making. The data analysis was processed through combination of deductive and inductive methods. After the interviews transcriptions it was made a content analysis through the software QSR NVivo 11. With the results it was revealed that coaches’ share similar ideas to prepare their teams being the main focus the own team identity and composure and only after it is considered the opposition team behavior and composure. It was also possible to identify clear coaching behavioral signs possible to be structured as cues and guiding lines for their decision-making process and actions before and during competitive moments. Trough the thinking process identification and guiding lines that support the action and decisions from futsal coaches’ we consider that it’s possible the development of coaching education curriculums adjusted to the competitive moment needs and improving the knowledge and effectiveness in the preparation and resolution of momentary problems of futsal game.